2004
DOI: 10.1002/kin.10162
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants for reaction of 1,2‐dimethylimidazole with benzyl bromide in ionic liquids and organic solvents

Abstract: The rate constant for the Menschutkin reaction of 1,2-dimethylimidazole with benzyl bromide to produce 3-benzyl-1,2-dimethylimidazolium bromide was determined in a number of ionic liquids and molecular organic solvents. The rate constants in 12 ionic liquids are in the range of (1.0-3.2) × 10 −3 L mol −1 s −1 and vary with the solvent anion in the order (CF 3 SO 2 ) 2 N − < PF 6 − < BF 4 − . Variations with the solvent cation (butylmethylimidazolium, octylmethylimidazolium, butyldimethylimidazolium, octyldimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…For the fastest reactions, one might predict with reasonable confidence a diffusion-controlled rate curtailed in proportion to the greater viscosity ionic liquids are known to possess, although work by Neta et al cautions against the over-interpretation of classical formulae commonly applied to molecular solvents for estimating such rates. [10] Activated processes, however, could be either driven or impeded depending on specific solvation effects, and while the dimerisation of benzaldehyde radical anions and the reaction of 1,2-dimethylimidazole with benzyl bromide in RTILs display rate constants comparable to those in polar, aprotic solvents, [9,11] Hapiot has reported both a significant decrease and increase in the rates of various electrodimerisation reactions, rationalised in each case using ion-association arguments. [5,7] In all these examples, however, the rate constants did not differ by more than one order of magnitude from the equivalent value in acetonitrile, where reported.…”
Section: Introductionmentioning
confidence: 94%
“…For the fastest reactions, one might predict with reasonable confidence a diffusion-controlled rate curtailed in proportion to the greater viscosity ionic liquids are known to possess, although work by Neta et al cautions against the over-interpretation of classical formulae commonly applied to molecular solvents for estimating such rates. [10] Activated processes, however, could be either driven or impeded depending on specific solvation effects, and while the dimerisation of benzaldehyde radical anions and the reaction of 1,2-dimethylimidazole with benzyl bromide in RTILs display rate constants comparable to those in polar, aprotic solvents, [9,11] Hapiot has reported both a significant decrease and increase in the rates of various electrodimerisation reactions, rationalised in each case using ion-association arguments. [5,7] In all these examples, however, the rate constants did not differ by more than one order of magnitude from the equivalent value in acetonitrile, where reported.…”
Section: Introductionmentioning
confidence: 94%
“…21 The E T (30) scale 20 is based upon the wavelength of absorption of solvatochromatic dye 3 and has found applications in analytical chemistry (where it can be used to predict changes in retention time, and to measure solvent water content) 22 and chemical kinetics (to predict changes in the rates of S N 2 reactions 23 and ligand exchange processes 24 ).…”
Section: 14mentioning
confidence: 99%
“…Ionic liquids were also a subject of interest in advanced oxidation processes, not as target solutes however but as a novel reaction media for decomposition of various contaminants including CCl 4 , benzophenone, quinones or chlorinated phenols [21][22][23][24]. It was found that formation of stable radiolysis intermediates of ionic liquids may lead to their resistance towards oxidation, thus making them privileged for type of applications.…”
Section: Introductionmentioning
confidence: 99%